Wykorzystanie metody service blueprinting w tworzeniu innowacji usługowych - Anetta Pukas (Ekonomiczne Problemy Usług, 2018)
The issue of generation and implementation of innovation as the competence of the ever-growing service sector is becoming an increasingly research topic in the field of management sciences. Due to the specificity of service innovation and the fact that service requires coordinating multiple processes at different levels of the company and customer contact, it is suggested to use in the design of new services the methods and techniques dedicated to this sector. The aim of the article is to identify the possibility of using the Service Blueprinting method in contemporary processes of creating innovative solutions in the services sector. The method of systematic and critical analysis of domestic and foreign literature was used to achieve the aim of the work. As a result of the study, the author presents the concept of developing the SB method and using it in creating service innovations.